PENERAPAN MEDIA PEMBELAJARAN DIGITAL BERBASIS WEBSITE SEBAGAI UPAYA PENINGKATAN MINAT BELAJAR PESERTA DIDIK KELAS VI SD INPRES MINASA UPA KOTA MAKASSAR - Andi Miftahul Jannah; Aliem Bahri (STKIP Subang, 2024)
This Classroom Action Research (CAR) aimed to enhance the learning motivation of sixth-grade students at SD Inpres Minasa Upa through the implementation of a web-based digital learning platform. The study was conducted in two cycles, each comprising three meetings. The first cycle involved the introduction of the website and its basic features, while the second cycle introduced additional interactive elements such as educational games and project-based tasks. The results indicated a significant improvement in student engagement, increasing from 55% at the end of the first cycle to 80% by the end of the second cycle, and an enhancement in task quality, with average scores rising from 65 to 80. Student feedback also showed an increase in satisfaction from 60% to 85%. These findings suggest that well-designed digital learning media can effectively boost student interest and motivation. The research demonstrates that continuous adjustments and interactive features positively impact student engagement and academic outcomes.